Comportamento do consumidor no processo de compra e a influência das ferramentas de inteligência artificial - Silva, Wallysson Klebson de Medeiros (2023)
The main objective of this thesis was to examine the influence and potential behavior changes of consumers when using Artificial Intelligence (AI) tools in their purchase journey. The research was conducted in two methodological stages: a qualitative approach with 16 semi-structured interviews, and a quantitative approach with a survey of 414 participants. Qualitative data analysis was conducted using content analysis with the support of Atlas.ti software. In the quantitative approach, statistical techniques were used, including Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM), with the assistance of AMOS and SPSS software. Additionally, the transtheoretical model of behavior was used as a complement to the quantitative research. Based on the qualitative findings, reflections were made on how AI assists in the stages of the consumer journey, as well as the need to add the construct of "resistance" to the theoretical model of Acceptance of Use of Artificial Intelligence Devices (AUID). From the results of the quantitative research, it was possible to verify that social influence, anthropomorphism, and consumer resistance are the most preponderant antecedent factors for measuring perceived performance expectation and, consequently, emotion that collaborates in the consumer's willingness to accept the use of AI devices in their purchase journey. In addition, emotion is negatively related to the consumer's objection to accepting the use of AI devices in the purchase process. Consumer behavior change stages were also identified, indicating that individuals in certain stages have psychological characteristics and motivations that differ from those in other stages. Thus, it can be said that this research contributed to the understanding of consumer behavior in the purchase process with the assistance of AI tools, bringing relevant theoretical and practical implications for the field of administration and marketing research. It is hoped that the results obtained can serve as a basis for future studies on the subject and assist companies and professionals in the area in understanding and leveraging the potential of AI to improve the consumer experience in their purchase journey.